Norwegian teachers: competencies perceived as important for inclusive education - Kuyini, Ahmed Bawa (2023)
This study explored what teaching competencies teachers in Received 27 January 2022 Norwegian Junior high and Senior high schools perceived as Accepted 2 August 2023 important to their teaching in inclusive education (IE) classrooms. The participants (N-206) responded to a 15-item survey Perceived KEYWORDS Norway; inclusive education; Competencies for Inclusive Teaching Scale focussed on teachers’ competencies competencies, and one open-ended question about the resources that will support effective teaching. The results were analysed using descriptive statistics, t-tests, ANOVA and qualitative procedures. The results showed that participants identified, among others, competencies such as Modifying learning content to meet students’ different learning needs, Identifying special needs and Scaffolding strategies as the most important. The key resources teachers identified to enable implementation of IE included training in special education, more time for teaching, more pedagogical discussions sessions and school leadership. The implications for IE practice in Norway are discussed in relation current arrangements in schools and teacher training.